Nanoplastics causes extensive congenital malformations during embryonic development by passively targeting neural crest cells. (March 2023) - Wang, Meiru; Rücklin, Martin; Poelmann, Robert E.; de Mooij, Carmen L.; Fokkema, Marjolein; Lamers, Gerda E.M.; de Bakker, Merijn A.G.; Chin, Ernest; Bakos, Lilla J.; Marone, Federica; Wisse, Bert J.; de Ruiter, Marco C.; et al.
Highlights: Polystyrene nanoplastics cause a wide spectrum of severe congenital malformations in the chick embryo. We provide the first evidence that nanoplastics cause severe defects in the heart and great vessels. We show that the mechanism of toxicity of nanoplastics is the binding of nanoplastics to neural crest cells. This is the first evidence that nanoplastics disrupt the migration and survival of an embryonic population of stem cells. Abstract: Nanomaterials are widespread in the human environment as pollutants, and are being actively developed for use in human medicine. We have investigated how the size and dose of polystyrene nanoparticles affects malformations in chicken embryos, and have characterized the mechanisms by which they interfere with normal development. We find that nanoplastics can cross the embryonic gut wall. When injected into the vitelline vein, nanoplastics become distributed in the circulation to multiple organs. We find that the exposure of embryos to polystyrene nanoparticles produces malformations that are far more serious and extensive than has been previously reported. These malformations include major congenital heart defects that impair cardiac function. We show that the mechanism of toxicity is the selective binding of polystyrene nanoplastics nanoparticles to neural crest cells, leading to the death and impaired migration of those cells. Consistent with our new model, most of the malformations seen in this study are in organs that depend for their normal development on neural crest cells. These results are a matter of concern given the large and growing burden of nanoplastics in the environment. Our findings suggest that nanoplastics may pose a health risk to the developing embryo.